Ecosystem Services of Ecosystem Approach to Mariculture: Providing an Unprecedented Opportunity for the Reform of China’s Sustainable Aquaculture - Zhou, Xijie; Fang, Jinghui; Shi, Siyuan; Yang, Ling; Xie, Bin; Huang, Lingfeng (Frontiers in Marine Science, 2022)
China is the biggest provider of mariculture products, and the industry is still growing rapidly. Increasing scientific evidence indicates that mariculture may provide valuable ecosystem goods and services in China. Here, we performed a systematic literature review of studies with the aim of understanding the ecosystem services of mariculture and a comprehensive review of ecosystem approaches that may improve mariculture ecosystem services and goods in China. We highlight four ecosystem services functions in China, including food supply, nutrient extraction, carbon sequestration, and biodiversity conservation. Given the further reform of China’s mariculture, we outlined several ecosystem approaches including integrated multi-trophic aquaculture (IMTA), carrying capacity assessment and monitoring, marine spatial planning, and waste treatment and recirculating mariculture system. We conclude that the ecosystem services of the ecosystem approach to mariculture provide an unprecedented opportunity for the reform of China’s sustainable aquaculture. Finally, a synthesis of sustainable development of mariculture, along with the five recommendations for future mariculture development in China, is outlined.